AUTOMATION OF INTRODUCTION OF TICKET COUPONS AIRLINES TO THE CORPORATE DATABASE - Mazur, V. I.; Suraev , V. F.; Ivankevich , O. V.; Mazur , O. Yu. (Problems of Informatization and Management, 2005)
The main theoretical elements of the problem of creating electronic document management systems at the enterprise, as well as the practical implementation and maintenance of automation system for entering airline ticket coupons in the airline on the example of the application software created by the authors of the article.